Some quantitative methods for allocating human resources in the manufacturing sector - Haider Younis Kadhim Al-Mousous; Hussein Dekan Darwish (Iraqi Journal for Administrative Sciences, 2024)
Industry is the core of the development process. Some even say that industry is the only way to achieve comprehensive economic and social development, as industrial activity constitutes an important and pivotal pillar in bringing about economic development through the development of national income and the formation of added values, as it includes a long and diverse series of production processes. Which in turn ensures a high rate of economic growth through which the material and human resources available in the country can be mobilized in an optimal manner. The industrial sector can be considered among the sectors most qualified to lead the economy in any country, especially developing countries.